GEODESIC OBSERVATIONS OF SUBSIDENCE OF BUILDING STRUCTURES OF THE STATE SPECIALIZED "CHERNOBYL NUCLEAR POWER PLANT" ENTERPRISES - Тітова, Світлана; Мординська, Анастасія (SWorldJournal, 2023)
The paper examines the theoretical basis for determining the subsidence of construction structures of the state-owned specialized enterprise "Chernobyl Nuclear Power Plant" by geodetic methods, as well as substantiates the methodological basis for choosi